Energy-efficient biogas production from co-digestion of food waste and sewage sludge via kinetic modeling and exergy analyses - Tunay, Dogukan; Yildirim, Oznur; Ozkaya, Bestami (SPRINGER, 2025)
Co-digestion of the waste is used for the increasing biogas production performance frequently. Response surface methodology and exergy analysis for the co-digestion potential of the food waste and sewage sludge occurred. Thus, the most suitable conditions were examined statistically and energy efficiently. The highest biogas production was found as 484 mL per g VS for the thermophilic condition with F/I ratio of 3 and food waste-to sewage sludge ratio 1:1. When the energy and exergy performance of thermophilic and mesophilic conditions were compared, the most energetically efficient conditions were 45 degrees C, F/I ratio of 5 and food-to-total substrate ratio of 1:2. In the study, total energy and biogas efficiencies were found that the thermophilic conditions in which temperature 55 degrees C, F/I ratio of 1 and food-to-total substrate ratio of 1:3 were the best operational conditions (effectiveness: 63.8%, exergy efficiency 42.2% and integrated efficiency 26.9%). These statistical calculations and energy balances can change according to the substrates and may contribute to the energy production potential of the biogas plants by considering the most efficient operational conditions.
Keywords: Food waste; Waste management; Co-digestion; Exergy; Design of experiment; SURFACE METHODOLOGY RSM; ANAEROBIC-DIGESTION; METHANE PRODUCTION; CIRCULAR ECONOMY; OPTIMIZATION; TEMPERATURE; PERFORMANCE; IMPROVE; Science & Technology - Other Topics; Environmental Sciences & Ecology